Impacts of varying day and night environmental conditions on cotton flowering, yield, and fiber quality - Thenveettil, Naflath; Allam, Manoj Kumar Reddy; Anapalli, Saseendran S.; Reddy, Krishna N.; Gao, Wei; Reddy, K. Raja (Frontiers in Plant Science, 2025)
IntroductionIncreases in the frequency of higher-than-optimum air temperatures can substantially reduce cotton production. Little is known about the influence of different combinations of day/nighttime temperature on cotton flowering and boll maturation under ambient and elevated CO2 conditions.MethodsThis study examined the impacts of air temperature variations on the morphology of cotton flowers and seed yield under air CO2 concentrations at 425 ppm (ambient, aCO2) and elevated at 725 ppm (eCO2) in controlled Soil-Plant Atmospheric Research (SPAR) chambers. The four temperature conditions were: optimum (OT; 33/21°C, day/night), high temperature (HT; 36/24°C, day/night), high nighttime (OT+HNT; 33/24 °C, day/night), and high day/nighttime (HT+HNT; 36/28 °C, day/night).ResultsVarious reproductive and seed yield traits, as well as the phenology of the plants, differed significantly (p < 0.001) under the treatments. The boll maturation period significantly decreased in plants grown under HT+HNT, with only 39 days under aCO2 and 38 days under eCO2 compared to 47 days at OT. In the HT and OT+HNT conditions, the duration was 42 days at aCO2 and 46 days at eCO2, as opposed to 41 and 44 days, respectively, under aCO2. Furthermore, there was a significant reduction in the number of pollen grains per anther, 13% for OT+HNT, 24% for HT, and 39% for HT+HNT, relative to OT treatments. The seed cotton weight also showed a drastic decline, decreasing from 105 g plant-1 under OT to 90 g under OT+HNT, 47 g under HT, and 12 g plant-1 under HT+HNT conditions. In the HT+HNT environment, lint percentage and seed weight per plant were reduced by 26% and 86%, respectively, when compared to OT. The eCO2 did not alleviate the reductions in cotton yield caused by higher air temperature exposure.DiscussionThis study highlights that high air temperature induces flower abscission and anther indehiscence, while diverting biomass allocation towards vegetative organs. The resulting source-sink imbalances between vegetative and reproductive structures resulted in significant reductions in seed and lint yield and growth patterns across CO2 and temperature environments. These findings provide insights into cotton management strategies under future environmental scenarios.